Detection of antibiotic residues in locally raw milk by using high performance liquid chromatography at different seasons and the effect of heat treatment on their concentration: Najim Hadi Najim and Ahmed Salman Moqef Al- kurashi - Al- kurashi, Ahmed Salman Moqef (The Iraqi Journal of Veterinary Medicine, 2018)
The aim of this study was to determine the level of antibiotics residues in the locally produced cows raw milk as well as to evaluate the effect of different commercial heat treated process on the level of antibiotics residues in milk. A total of 52 locally produced milk samples were collected from apparently healthy cows in AL-Fudhailia village, milk cans (50 Kg), bulk milk tanks (1, 5 and 10 tons) which belonged to the milk reception and collection centers and dairy plants in Baghdad were collected during beginning of December 2015 to the end of April 2016. Results revealed by using high performance liquid chromatography that there was a significant seasonal variation in the residual concentration of each detected antibiotic in milk samples, where it was found that all cow’s milk samples had significantly higher concentrations of antibiotic residues in spring than in winter seasons. Generally by excluding both the season and the kind of antibiotic, it was found that milk samples that were collected from 50 Kg milk cans recorded significantly highest antibiotic residues followed by bulk milk tanks of 1 and 5 tons in comparison to 10 tons. Antibiotics recovery experiment was conducted by spiking the bovine milk samples with Known concentrations four ß-lactams (Benzylpencillin, Cloxacillin, Amoxcilin, Ampcilline) and other five detected antibiotics and then exposed to one of the three different commercial heat treatments. The results showed that the pasteurization process (63°C/30 min.) a slight inactivation of four ß-lactams and other five detected antibiotics, whereas 80°C/5 min. high degree of antimicrobial loss at the rate of 89% and 82%. However, boiling at 100°C/5 min, high degree of antimicrobial loss at the rate of 100% and 90% respectively.